Images generated by the global media (CNN and BBC) regarding the developed and developing countries a content analysis - Venzon, Enrico Thomas V.; Paragas, Fernando DL Cruz; dela Cruz, Marichelle S.D.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This research is focused on the images generated by the global media, particularly CNN and BBC, regarding the developed and developing countries. Through the use of content analysis, the researcher aimed to find out if the imbalance in the international flow of communication between the developed and developing countries. Through the use of content analysis, the researcher aimed to find out if the imbalance in the international flow of communication between the developed and developing nations still exist. The coverage and reporting of CNN and BBC have been analyzed to see whether these two networks contribute to the imbalance of information flow between the developed and developing countries in terms of their programming. The study framework used for this study is Mowlana's Model of International Flow of Information. The results show that CNN and BBC is seen to report more on political and governmental affairs in their coverage of events in the developed and developing countries. Stories regarding conflicts like wars, crime, violence and other violent acts are given also much airtime. Other stories dealing with the culture of people like the arts, literature, music, and other traditions of different nations are also given importance, but less, in their programming. With respect to the coverage of these two networks in terms of the origin of their stories, CNN and BBC reported more on the developed countries than with the developing ones. This finding lends credence to the concerns of developing countries that the mass of developed countries tended to underreport on the developing nations. Thus, CNN and BBC seem to contribute to the imbalance of information flow. Another concern of the developing nations in the coverage of news is in terms of the quality of the reporting. The data gathered in this study does not indicate a tendency for CNN and BBC to treat the reports about the developed countries more favorably than the developing nations. Hopefully, this study will help media practitioners and mass communication students see the need for more balance and responsible coverage of events in order to achieve greater international understanding and cooperation.
Vita.
Undergraduate thesis
Keywords: Developed countries -- Press coverage; Developing countries -- Press coverage; Cable News Network(Television Network) -- Press coverage; British Broadcasting Corp. (Television Network) -- Press coverage